Ответы и объяснения

2012-10-05T13:35:45+04:00

    х         х+2  

 4      +  2         -     12  =    0

 

   2 х         х    2 

2        +  2   2      -     12  =    0

        х  2             х

   ( 2   ) +   4* 2      -     12  =    0

                  х

Замена    2      =  y


у²  + 4у - 12 = 0


По т.Виета   у₁ + у₂ = -4        у₁у₂ = -12  =>   у₁= -6,  у₂=2         => 

   х                                                   х

2     =   -6                     или           2     =  2
нет решений                                 х = 1


Ответ: 1.